Authorization of the Barring Order by the Investigating Judge: Problems of Legislative Regulation - BAKYT, Aidar (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The article considers the issues of functioning in the criminal justice process of modern Kazakhstan of the institution of judicial control over pre-trial investigation. The study objective is to identify the problems of legislative regulation of the procedure for the use by the investigating judge of procedural coercion in the form of a barring order. As part of the study, the author provides key approaches to defining the essence of judicial control over pre-trial investigation, defines the procedural status of the investigating judge and classifies his/her powers. The analysis of the current procedure for the use of a barring order as a coercive measure has allowed to develop specific approaches to the implementation of competent law enforcement, as well as proposals to improve the existing legislative procedures to address cases of undue restrictions on the rights of an individual in criminal proceedings.
Keywords: criminal procedure, judicial control, investigating judge, barring order, restraining order, protective order